Individually tailored vs. standardized substrate modification during radiofrequency catheter ablation for atrial fibrillation: a randomized study. Issue 11 (21st November 2017) - Kircher, Simon; Arya, Arash; Altmann, David; Rolf, Sascha; Bollmann, Andreas; Sommer, Philipp; Dagres, Nikolaos; Richter, Sergio; Breithardt, Ole-A; Dinov, Borislav; Husser, Daniela; Eitel, Charlotte; et al.
Abstract: Aims: This randomized single-centre study sought to compare the efficacy and safety of pulmonary vein isolation (PVI) plus voltage-guided ablation vs. PVI with or without linear ablation depending on the type of atrial fibrillation (AF). Methods and results: Overall, 124 ablation-naive patients with paroxysmal or persistent AF were randomized to PVI with (persistent AF) or without (paroxysmal AF) additional linear ablation (control group) vs. PVI plus ablation of low-voltage areas (LVAs) irrespective of AF type. Bipolar voltage mapping was performed during stable sinus rhythm. An LVA consisted of  ≥ 3 adjacent mapping points that each had a peak-to-peak amplitude ≤0.5 mV. After a mean follow-up of 12 ± 3 months, significantly more patients in the LVA ablation group were free from atrial arrhythmia recurrence >30 s off antiarrhythmic drugs (AADs) after a single procedure (primary endpoint) compared with control group patients [40/59 (68%) vs. 25/59 (42%), log-rank P  = 0.003]. Arrhythmia-free survival on or off AADs was found in 33/59 control group patients (56%) and in 41/59 LVA ablation group patients (70%) (adjusted log-rank P  = 0.10). During the 7 day Holter monitoring period at 12 months, significantly more patients in the LVA ablation group were free from arrhythmia recurrence on or off AADs [45/50 (90%) vs. 33/46 (72%), P  = 0.04]. No between-group differences were observed regarding procedure duration, fluoroscopy time, and major complications. Conclusion: In this single-centre study, individually tailored substrate modification guided by voltage mapping was associated with a significantly higher arrhythmia-free survival rate compared with a conventional approach applying linear ablation according to AF type.